أثر تغيرات أسعار النفط على سعر الصرف الحقيقي الفعلي في الدول المصدرة للنفط -دراسة حالة الجزائر في الفترة 1980-2023 - نفطي زوبير (جامعة الوادي University of Eloued, 2025)
تهدف هذه الدراسة للتعرف على أثر أسعار النفط على معدل السعر الحقيقي الفعلي في الجزائر للفترة الممتدة من 1980 إلى 2023، و باستعمال المنهج الوصفي التحليلي تم وصف مختلف الأدبيات النظرية الخاصة بالدراسة ، بالإضافة إلى جمع و تحليل مختلف البيانات المتعلقة بالمتغير خلال فترة الدراسة لتحديد الأثر القائم بينهما بتحديد العلاقة التي تربطهما ، لتتوصل الدراسة إلى نتائج أهمها أن هناك علاقة عكسية بين سعر النفط و سعر الصرف الفعلي الحقيقي خلال فترة الدراسة حيث أن سعر النفط يوثر إيجابا على سعر الصرف الفعلي الحقيقي ، فكلما واجهت الجزائر أزمة في سعر الصرف أدى إلى ارتفاع سعر الصرف الفعلي الحقيقي للدينار راجع ذلك لسلة العملات المتواجد بها. This study aims to identify the impact of oil prices on the real effective exchange rate in Algeria for the period from 1980 to 2023. Using a descriptive and analytical approach, various theoretical literature related to the study was described, in addition to collecting and analyzing various data related to the variable during the study period to determine the impact between them and the relationship between them. The study reached the most important results, namely that there is an inverse relationship between the price of oil and the real effective exchange rate during the study period, as the price of oil has a positive impact on the real effective exchange rate. Whenever Algeria faces an exchange rate crisis, this leads to an increase in the real effective exchange rate of the dinar, due to the currency basket it contains.
ماستر العلوم التجارية
Keywords: سعر الصرف; الفعلي الحقيقي; Exchange rate; oil price; real effective exchange rate.